A flexible high thermal conductivity boron nitride ceramic-based film and preparation method thereof

Through electrospinning technology, the boron nitride precursor is overlapped with one-dimensional flexible high-thermal conduction material to form a porous ceramic film, solving the problem of the contradiction between thermal conductivity and flexibility of flexible nanoceramic materials, and achieving high thermal conductivity and good flexibility Take into account both.

CN116903380BActive Publication Date: 2024-12-17XI AN JIAOTONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310759189.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2024-12-17
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

When existing flexible nanoceramic materials improve thermal conductivity, their flexibility is significantly reduced, making it difficult to take into account both thermal conductivity and flexibility.

Method used

Electrospinning technology is used to overlap the whiskers of the boron nitride precursor with one-dimensional flexible and highly thermally conductive materials (such as carbon nanotubes or boron nitride nanotubes), and the porous ceramic film is formed through high-temperature ceramicization treatment to realize the network interoperability of nanomaterials The connecting structure combines "soft-hard" chemical combination and coordinated deformation to improve thermal conductivity and maintain flexibility.

Benefits of technology

A flexible boron nitride ceramic film with high thermal conductivity and good flexibility was prepared, with thermal conductivity inside and outside the surface and outside respectively, satisfying thermal conductivity and flexibility. Take into account both.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116903380B_ABST
    Figure CN116903380B_ABST
Patent Text Reader

Abstract

The present invention discloses a flexible high thermal conductivity boron nitride ceramic-based film and a preparation method thereof, which belongs to the technical field of flexible high thermal conductivity material preparation. The preparation method comprises the following steps: first, boron nitride precursor whiskers are prepared using boric acid and melamine as raw materials; then, boron nitride precursor whiskers, one-dimensional flexible high thermal conductivity material and binder polyvinyl pyrrolidone are used as raw materials, and electrostatic spinning, carbon removal treatment and high-temperature ceramic heat treatment are performed to obtain a method for preparing a flexible high thermal conductivity boron nitride ceramic-based film. The present invention uses boron nitride to prepare a high thermal conductivity porous ceramic film, and its advantage is that the hard boron nitride whiskers converted by ceramicization are combined with the "soft-hard" reactive properties of the original one-dimensional flexible high thermal conductivity material, and a ceramic film with high thermal conductivity and good flexibility can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible high thermal conductivity material preparation, and relates to a flexible high thermal conductivity boron nitride ceramic-based film and a preparation method thereof. Background Art

[0002] The most reported flexible porous ceramics are ceramic aerogels, foams, sponges or flexible papers constructed with ultra-long 1D nanowires (fibers) or 2D nanoribbons. However, despite the excellent flexibility of the above ceramics, their thermal conductivity is low. The reason is that this type of material is composed of nanoceramics. The ceramicization temperature is low (≤1400°C) and the crystallinity is poor. Its flexibility comes from the synergistic effect of the internal structural defects of the nanoceramic material (such as amorphous, high dislocation density, lattice distortion, etc.), and these defects make the intrinsic thermal conductivity of the material very low. In order to improve the intrinsic thermal conductivity of ceramics, it is necessary to increase the crystallinity of the ceramics by increasing the heat treatment temperature of the nanoceramics, but this will cause a significant decrease in the overall flexibility of the nanoceramic material.

[0003] Regarding the preparation method of nano-flexible boron nitride (BN), the current research is more about the preparation of BN whiskers or fibers by inorganic precursor self-assembly combined with in-situ conversion (firstly, boric acid and melamine are used as raw materials to prepare precursor nano whiskers, and then heat-treated to convert them into BN whiskers). This method is simple and easy, and the whiskers have good flexibility below 1400°C. However, the flexible boron nitride has low crystallinity, resulting in low intrinsic thermal conductivity. When the heat treatment temperature of BN whiskers is further increased (>1400°C), its intrinsic thermal conductivity is improved, but it becomes significantly harder and more brittle. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a flexible high thermal conductivity boron nitride ceramic-based film and a preparation method thereof to solve the problem of the contradiction between flexibility and thermal conductivity of nano ceramic films in the prior art. The porous ceramic film prepared by the present invention has high thermal conductivity and good flexibility.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film comprises the following steps:

[0007] Step 1, dissolving melamine and boric acid in water to obtain a mixed solution, heating the mixed solution and stirring it, then aging and filtering it in sequence, and drying the filtered product to obtain boron nitride precursor whiskers;

[0008] Step 2, placing the boron nitride whiskers in anhydrous ethanol for ultrasonic dispersion, adding a one-dimensional flexible high thermal conductive material for ultrasonic dispersion, and then adding a binder, stirring to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning treatment, and the spun material is dried, decarbonized and ceramicized by heat treatment to obtain a boron nitride ceramic-based film.

[0009] A further improvement of the present invention is:

[0010] Preferably, in step 1, the concentration of melamine in the mixed solution is 0.05-0.2M.

[0011] Preferably, in step 1, the molar ratio of melamine to boric acid is 1:1-1:4.

[0012] Preferably, in step 1, the stirring temperature is 80-100° C. and the aging time is 20-30 h.

[0013] Preferably, in step 1, the drying temperature is 70-100° C. and the drying time is 30-40 h.

[0014] Preferably, in step 2, the concentration of boron nitride whiskers in anhydrous ethanol is 0.1-0.2 g·mL -1 ; The concentration of one-dimensional flexible high thermal conductive material in anhydrous ethanol is 0.005-0.1g·mL -1 The concentration of polyvinyl pyrrolidone in anhydrous ethanol is 0.05-0.10 g·mL -1 .

[0015] Preferably, in step 2, the one-dimensional flexible high thermal conductivity material is carbon nanotubes or boron nitride nanotubes.

[0016] Preferably, in step 2, the temperature of the decarbonization treatment is 400-600° C. and the time is 0.5-4 h.

[0017] Preferably, in step 2, the heating rate of the ceramic heat treatment is 2-10°C / min, the final temperature is 1400-1800°C, and the time is 0.5-6h.

[0018] A flexible high thermal conductivity boron nitride ceramic-based film prepared by any one of the preparation methods described above is composed of boron nitride whiskers and nanotubes overlapped, and the nanotubes are carbon nanotubes or boron nitride nanotubes.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention discloses a method for preparing a flexible high thermal conductivity boron nitride ceramic-based film, the preparation method comprising the following steps: firstly, using boric acid and melamine as raw materials to prepare boron nitride precursor whiskers; further, using boron nitride precursor whiskers, one-dimensional flexible high thermal conductivity material and binder polyvinyl pyrrolidone as raw materials, through electrostatic spinning, carbon removal treatment (removal of binder) and high-temperature ceramic heat treatment, a method for preparing a flexible high thermal conductivity boron nitride ceramic-based film is obtained. During the preparation process, electrostatic spinning helps to increase the contact between the boron nitride precursor whiskers and the one-dimensional flexible high thermal conductivity material. During the ceramic transformation process of the precursor whiskers, through material diffusion migration, reactive bonding with the one-dimensional flexible high thermal conductivity material is achieved, and finally a nanomaterial network interconnection structure is formed. 2) The boron nitride whiskers obtained by high-temperature ceramic treatment (>1400°C) are high thermal conductivity hard phases, and the one-dimensional flexible high thermal conductivity material is introduced into the initial raw material. Through the "soft-hard" chemical combination and the coordinated deformation of the soft phase, the flexibility and high thermal conductivity of the overall material are achieved.

[0021] The invention also discloses a flexible high-thermal-conductivity boron nitride ceramic-based film, which is overlapped with each other by nanotubes and boron nitride whiskers to form a film with flexibility and high thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD spectrum of the flexible high thermal conductivity boron nitride ceramic-based film prepared in Example 1.

[0023] Figure 2 This is a SEM image of the flexible and highly thermally conductive boron nitride ceramic-based film prepared in Example 1.

[0024] Figure 3 This is a macroscopic picture of the flexible high thermal conductivity boron nitride ceramic-based film prepared in Example 1, indicating that it has bendable flexibility. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:

[0026] One embodiment of the present invention discloses a method for preparing a flexible high thermal conductivity boron nitride ceramic-based film, which mainly includes the following steps:

[0027] (1) Melamine and boric acid are dissolved in deionized water, the temperature is increased and the mixture is stirred, and boron nitride precursor whiskers are obtained after aging, filtering and drying.

[0028] Specifically, the concentration of melamine is 0.05-0.2 M, and the molar ratio of melamine to boric acid is 1:1-1:4.

[0029] Specifically, the temperature during the stirring process is 80-100° C., the aging time is 20-30 hours, the drying temperature is 70-100° C., and the drying time is 30-40 hours.

[0030] (2) Since boron nitride precursor whiskers are difficult to disperse, the boron nitride precursor whiskers are first placed in an anhydrous ethanol solution for ultrasonic dispersion to obtain a uniform dispersion of the boron nitride precursor, and then a one-dimensional flexible high thermal conductivity material is added for ultrasonic dispersion again to obtain a uniform dispersion of the boron nitride precursor and the one-dimensional flexible high thermal conductivity material. Finally, a binder, polyvinyl pyrrolidone, is added and stirred thoroughly to obtain a spinning solution, which is subjected to electrospinning, drying, carbon removal (removal of the binder), and high-temperature ceramic heat treatment to obtain a high thermal conductivity porous ceramic film constructed by a one-dimensional nanomaterial soft-hard combination.

[0031] Specifically, the concentration of boron nitride precursor whiskers in the spinning solution is 0.1-0.2 g·mL -1 , the concentration of one-dimensional flexible high thermal conductive material is 0.005-0.5g·mL -1 The concentration of the binder polyvinyl pyrrolidone is 0.05-0.10 g·mL -1 .

[0032] Specifically, the one-dimensional flexible high thermal conductivity material is carbon nanotubes, boron nitride nanotubes, etc.

[0033] Specifically, the decarbonization temperature of the electrospinning film is 400-600°C and the time is 0.5-4h.

[0034] Specifically, the heating rate of the electrospun film high temperature ceramic heat treatment is 2-10°C / min, the final temperature is 1400-1800°C, and the holding time is 0.5-6h. Finally, a high thermal conductivity porous ceramic film with nanotubes and boron nitride whiskers overlapping each other is obtained.

[0035] The following is further described in conjunction with specific embodiments:

[0036] Example 1

[0037] A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film comprises the following steps:

[0038] (1) Melamine and boric acid are dissolved in 1 L of water at a molar ratio of 1:3, wherein the molar concentration of melamine is 0.16 M, placed in an oil bath at 95° C. and stirred, stirred until clear and then stirred for 30 min, cooled at room temperature and aged for 24 h, filtered, and dried in a forced air drying oven at 80° C. for 36 h to obtain boron nitride precursor whiskers;

[0039] (2) Weigh 1.4 g of the boron nitride precursor whiskers obtained in step (1) and place them in 10 mL of anhydrous ethanol solution for ultrasonic dispersion for 15 min, then add 0.09 g of carbon nanotubes and ultrasonically disperse them again for 15 min, and finally add 0.79 g of binder polyvinyl pyrrolidone, stir well to obtain a spinning solution, and perform electrospinning at a spinning voltage of 18 kV and a propulsion speed of 2.5 mL / h. Then dry at 80° C. for 2 h to obtain a precursor film;

[0040] (3) heating the film obtained in (2) to 500°C in a muffle furnace at a heating rate of 2.5°C / min, keeping the temperature for 2 hours, and cooling the film in the furnace to stabilize and remove carbon;

[0041] (4) The film sample obtained in (3) was placed in a tubular furnace and heated to 1400°C at a heating rate of 5°C / min and kept at that temperature for 0.5 h to perform high-temperature ceramic heat treatment to obtain a high thermal conductivity porous ceramic film.

[0042] This embodiment obtains a flexible high thermal conductivity boron nitride ceramic-based film, such as Figure 1 The XRD structure characterization of this film shows that it is a three-dimensional porous structure composed of carbon nanotubes and boron nitride nanowhiskers (such as Figure 2 ) and has a certain degree of flexibility (such as Figure 3 ). After impregnation with polymer, the in-plane thermal conductivity of the composite material is 2.47 W·m -1 K -1 , the out-of-plane thermal conductivity is 0.67 W·m -1 K -1 .

[0043] Example 2

[0044] A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film comprises the following steps:

[0045] (1) Melamine and boric acid are dissolved in 1 L of water at a molar ratio of 1:3, wherein the molar concentration of melamine is 0.16 M, placed in an oil bath at 95° C. and stirred, stirred until clear and then stirred for 30 min, cooled at room temperature and aged for 24 h, filtered, and dried in a forced air drying oven at 80° C. for 36 h to obtain boron nitride precursor whiskers;

[0046] (2) Weigh 1.8 g of the boron nitride precursor whiskers obtained in step (1) and place them in 10 mL of anhydrous ethanol solution for ultrasonic dispersion for 15 min, then add 0.09 g of carbon nanotubes and ultrasonically disperse them again for 15 min, and finally add 0.79 g of binder polyvinyl pyrrolidone, stir well for 2 h to obtain a spinning solution, and perform electrospinning at a spinning voltage of 18 kV and a propulsion speed of 2.5 mL / h. Then dry at 80° C. for 2 h to obtain a precursor film;

[0047] (3) The film obtained in (2) was heated to 500°C in a muffle furnace at a heating rate of 2.5°C / min, kept at this temperature for 2 h, and then cooled in the furnace for stabilization and decarbonization.

[0048] (4) The film sample obtained in (3) is placed in a tubular furnace and heated to 1600°C at a heating rate of 5°C / min, and kept at this temperature for 1 hour to perform high-temperature ceramic heat treatment to obtain a boron nitride nanotube-boron nitride composite film.

[0049] The one-dimensional nanomaterial soft-hard combination high thermal conductivity porous ceramic film obtained in this embodiment has an in-plane thermal conductivity of 3.18 W·m after being impregnated with polymer. -1 K -1 , the out-of-plane thermal conductivity is 0.79 W·m -1 K -1 .

[0050] Example 3

[0051] A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film comprises the following steps:

[0052] (1) Melamine and boric acid are dissolved in 1 L of water at a molar ratio of 1:3, wherein the molar concentration of melamine is 0.16 M, placed in an oil bath at 95° C. and stirred, stirred until clear and then stirred for 30 min, cooled at room temperature and aged for 24 h, filtered, and dried in a forced air drying oven at 80° C. for 36 h to obtain boron nitride precursor whiskers;

[0053] (2) Weigh 1.4 g of the boron nitride precursor whiskers obtained in step (1) and place them in 10 mL of anhydrous ethanol solution for ultrasonic dispersion for 15 min, then add 0.12 g of carbon nanotubes and ultrasonically disperse them again for 15 min, and finally add 0.79 g of binder polyvinyl pyrrolidone, stir well to obtain a spinning solution, and perform electrospinning at a spinning voltage of 18 kV and a propulsion speed of 2.5 mL / h. Then dry at 80° C. for 2 h to obtain a precursor film;

[0054] (3) The film obtained in (2) was heated to 500°C in a muffle furnace at a heating rate of 2.5°C / min, kept at this temperature for 2 hours, and then cooled in the furnace for stabilization and decarbonization.

[0055] (4) placing the film sample obtained in (3) in a tube furnace and heating it to 1600° C. at a heating rate of 5° C. / min, and keeping it at that temperature for 2 h to perform high-temperature ceramic heat treatment to obtain a boron nitride nanotube-boron nitride composite film;

[0056] The method for preparing a flexible high thermal conductivity boron nitride ceramic-based film obtained in this embodiment has a composite material with an in-plane thermal conductivity of 4.82 W·m after being impregnated with a polymer.-1 K -1 , the out-of-plane thermal conductivity is 0.79 W·m -1 K -1 .

[0057] Example 4

[0058] A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film comprises the following steps:

[0059] (1) Melamine and boric acid are dissolved in 1 L of water at a molar ratio of 1:4, wherein the molar concentration of melamine is 0.05 M, placed in an oil bath at 90° C. and stirred, stirred until clear and then stirred for 30 min, cooled at room temperature and aged for 25 h, filtered, and dried in a forced air drying oven at 85° C. for 30 h to obtain boron nitride precursor whiskers;

[0060] (2) Weigh 1 g of the boron nitride precursor whiskers obtained in step (1) and place them in 10 mL of anhydrous ethanol solution for ultrasonic dispersion for 15 min, then add 0.05 g of carbon nanotubes and ultrasonically disperse them again for 15 min, and finally add 0.6 g of binder polyvinyl pyrrolidone, stir well for 2 h to obtain a spinning solution, and perform electrospinning at a spinning voltage of 18 kV and a propulsion speed of 2.5 mL / h. Then dry at 80° C. for 2 h to obtain a precursor film;

[0061] (3) The film obtained in (2) was heated to 600°C in a muffle furnace at a heating rate of 2.5°C / min, kept at this temperature for 3 hours, and then cooled in the furnace for stabilization and decarbonization.

[0062] (4) The film sample obtained in (3) is placed in a tubular furnace and heated to 1500°C at a heating rate of 10°C / min, and kept at this temperature for 3 hours to perform high-temperature ceramic heat treatment to obtain a boron nitride nanotube-boron nitride composite film.

[0063] Example 5

[0064] A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film comprises the following steps:

[0065] (1) Melamine and boric acid are dissolved in 1 L of water at a molar ratio of 1:1, wherein the molar concentration of melamine is 0.1 M, placed in an oil bath at 100° C. and stirred, stirred until clear and then stirred for 30 min, cooled at room temperature and aged for 20 h, filtered, and dried in a forced air drying oven at 90° C. for 40 h to obtain boron nitride precursor whiskers;

[0066] (2) Weigh 0.07 g of the boron nitride precursor whisker obtained in step (1) and place it in 10 mL of anhydrous ethanol solution for ultrasonic dispersion for 15 min, then add 0.1 g of boron nitride nanotubes and ultrasonically disperse it again for 15 min, and finally add 0.7 g of binder polyvinyl pyrrolidone, stir well for 2 h to obtain a spinning solution, and perform electrospinning at a spinning voltage of 18 kV and a propulsion speed of 2.5 mL / h. Then dry it at 80° C. for 2 h to obtain a precursor film;

[0067] (3) The film obtained in (2) was heated to 400°C in a muffle furnace at a heating rate of 2.5°C / min, kept at this temperature for 2 h, and then cooled in the furnace for stabilization and decarbonization.

[0068] (4) The film sample obtained in (3) was placed in a tubular furnace and heated to 1700°C at a heating rate of 2°C / min, and kept at that temperature for 4 hours to perform high-temperature ceramic heat treatment to obtain a boron nitride nanotube-boron nitride composite film.

[0069] Example 6

[0070] A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film comprises the following steps:

[0071] (1) Melamine and boric acid are dissolved in 1 L of water at a molar ratio of 1:2, wherein the molar concentration of melamine is 0.12 M, placed in an oil bath at 80° C. and stirred, stirred until clear and then stirred for 30 min, cooled at room temperature and aged for 30 h, filtered, and dried in a forced air drying oven at 95° C. for 38 h to obtain boron nitride precursor whiskers;

[0072] (2) Weigh 1.2 g of the boron nitride precursor whiskers obtained in step (1) and place them in 10 mL of anhydrous ethanol solution for ultrasonic dispersion for 15 min, then add 0.5 g of carbon nanotubes and ultrasonically disperse them again for 15 min, and finally add 0.5 g of binder polyvinyl pyrrolidone, stir well for 2 h to obtain a spinning solution, and perform electrospinning at a spinning voltage of 18 kV and a propulsion speed of 2.5 mL / h. Then dry at 80° C. for 2 h to obtain a precursor film;

[0073] (3) The film obtained in (2) was heated to 500°C in a muffle furnace at a heating rate of 2.5°C / min, kept at this temperature for 1 hour, and then cooled in the furnace for stabilization and decarbonization.

[0074] (4) The film sample obtained in (3) was placed in a tubular furnace and heated to 1800°C at a heating rate of 4°C / min and kept at that temperature for 5 hours to perform high-temperature ceramic heat treatment to obtain a boron nitride nanotube-boron nitride composite film.

[0075] Example 7

[0076] A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film comprises the following steps:

[0077] (1) Melamine and boric acid are dissolved in 1 L of water at a molar ratio of 1:1, wherein the molar concentration of melamine is 0.2 M, placed in an oil bath at 85° C. and stirred, stirred until clear and then stirred for 30 min, cooled at room temperature and aged for 22 h, filtered, and dried in a forced air drying oven at 100° C. for 38 h to obtain boron nitride precursor whiskers;

[0078] (2) Weigh 1.5 g of the boron nitride precursor whisker obtained in step (1) and place it in 10 mL of anhydrous ethanol solution for ultrasonic dispersion for 15 min, then add 0.05 g of carbon nanotubes and ultrasonically disperse it again for 15 min, finally add 0.8 g of binder polyvinyl pyrrolidone, stir well for 2 h to obtain a spinning solution, and perform electrospinning at a spinning voltage of 18 kV and a propulsion speed of 2.5 mL / h. Then dry it at 80° C. for 2 h to obtain a precursor film;

[0079] (3) The film obtained in (2) was heated to 450°C in a muffle furnace at a heating rate of 2.5°C / min, kept at this temperature for 0.5 h, and then cooled in the furnace for stabilization and decarbonization.

[0080] (4) The film sample obtained in (3) was placed in a tubular furnace and heated to 1550°C at a heating rate of 8°C / min, and kept at this temperature for 6 hours to perform high-temperature ceramic heat treatment to obtain a boron nitride nanotube-boron nitride composite film.

[0081] Example 8

[0082] A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film comprises the following steps:

[0083] (1) Melamine and boric acid are dissolved in 1 L of water at a molar ratio of 1:4, wherein the molar concentration of melamine is 0.15 M, placed in an oil bath at 90° C. and stirred, stirred until clear and then stirred for 30 min, cooled at room temperature and aged for 28 h, filtered, and dried in a forced air drying oven at 90° C. for 32 h to obtain boron nitride precursor whiskers;

[0084] (2) Weigh 1.9 g of the boron nitride precursor whisker obtained in step (1) and place it in 10 mL of anhydrous ethanol solution for ultrasonic dispersion for 15 min, then add 0.1 g of carbon nanotubes and ultrasonically disperse it again for 15 min, and finally add 1 g of binder polyvinyl pyrrolidone, stir well for 2 h to obtain a spinning solution, and perform electrospinning at a spinning voltage of 18 kV and a propulsion speed of 2.5 mL / h. Then dry it at 80° C. for 2 h to obtain a precursor film;

[0085] (3) The film obtained in (2) was heated to 550°C in a muffle furnace at a heating rate of 2.5°C / min, kept at this temperature for 4 hours, and then cooled in the furnace for stabilization and decarbonization.

[0086] (4) The film sample obtained in (3) is placed in a tubular furnace and heated to 1650°C at a heating rate of 6°C / min, and kept at this temperature for 2 hours to perform high-temperature ceramic heat treatment to obtain a boron nitride nanotube-boron nitride composite film.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a flexible high thermal conductivity boron nitride ceramic-based film, characterized in that: The following steps are involved: Step 1, dissolving melamine and boric acid in water to obtain a mixed solution, heating the mixed solution and stirring it, then aging and filtering it in sequence, and drying the filtered product to obtain boron nitride precursor whiskers; In step 1, the concentration of melamine in the mixed solution is 0.05-0.2 M; In step 1, the molar ratio of melamine to boric acid is 1:1-1:4; In step 1, the stirring temperature is 80-100°C and the aging time is 20-30h; In step 1, the drying temperature is 70-100°C and the drying time is 30-40h; Step 2, placing the boron nitride precursor whiskers in anhydrous ethanol for ultrasonic dispersion, adding a one-dimensional flexible high thermal conductive material for ultrasonic dispersion, and then adding a binder, stirring to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning treatment, and the spinning material is subjected to drying, carbon removal treatment and ceramic heat treatment to obtain a boron nitride ceramic-based film; In step 2, the one-dimensional flexible high thermal conductivity material is boron nitride nanotubes; In step 2, the decarbonization temperature is 400-600 °C and the time is 0.5-4 h; In step 2, the heating rate of the ceramic heat treatment is 2-10°C / min, the final temperature is 1400-1800°C, and the time is 0.5-6 h; In step 2, the concentration of boron nitride precursor whiskers in anhydrous ethanol is 0.1-0.2 g mL -1 ; The concentration of one-dimensional flexible high thermal conductive material in anhydrous ethanol is 0.005-0.1 g·mL -1 The concentration of the binder polyvinyl pyrrolidone in anhydrous ethanol is 0.05-0.10 g·mL -1 .

2. A flexible high thermal conductivity boron nitride ceramic-based film prepared by the preparation method of claim 1, characterized in that: The invention is composed of a boron nitride whisker and a nanotube overlapped with each other, wherein the nanotube is a boron nitride nanotube.

Citation Information

Patent Citations

  • Preparation method of boron nitride crystal whisker

    CN101550599A

  • Hexagonal boron-nitride material, preparation method and application of hexagonal boron-nitride material

    CN107376825A

  • High-thermal-conductivity electrostatic spinning film suitable for dye separation and preparation method and application

    CN107881651A

  • Flexible boron nitride nanotube inorganic diaphragm, preparation thereof and application of flexible boron nitride nanotube inorganic diaphragm in lithium secondary battery

    CN114421093A

  • Boron nitride nanofiber with high specific surface area as well as preparation method and application thereof

    CN115652478A